An experimental assessment of active and passive dispersal of red snow algae on the Harding Icefield, southcentral Alaska - Madeleine E. Rea; Roman J. Dial (Arctic, Antarctic, and Alpine Research)
Red snow algae seasonally color glacier and alpine snow surfaces with characteristic red blooms. These blooms significantly reduce the albedo of the snow surface resulting in increased snow ablation. The global cryosphere is sensitive to the melt effect of expansive reoccurring blooms; however, the primary dispersal path by which snow algae seasonally recolonize snow surfaces is currently unresolved. Using an experimental field approach that inhibited resurfacing populations with a physical barrier, then sampled algal surface abundance the following growing season, we assessed two pathways of algal surface colonization on the Harding Icefield, Alaska. Our results provide the first experimental depiction of active resurfacing as the primary pathway of seasonal snow surface colonization by red snow algae above the equilibrium line elevation on an Alaskan glacier. Results suggest that, at the peak of the growing season, 65 percent of surface abundance was derived from actively resurfacing cells and 35 percent from passively dispersing cells.